Functional characterization of an allatotropin receptor expressed in the corpora allata of mosquitoes - Nouzova, Marcela (2011)
Allatotropin is an insect neuropeptide with pleiotropic actions on a variety of different tissues. In the present work we describe the identification, cloning and functional and molecular characterization of an Aedes aegypti allatotropin receptor (AeATr) and provide a detailed quantitative study of the expression of the AeATr gene in the adult mosquito. Analysis of the tissue distribution of AeATr mRNA in adult female revealed high transcript levels in the nervous system (brain, abdominal, thoracic and ventral ganglia), corpora allata-corpora cardiaca complex and ovary. The receptor is also expressed in heart, hindgut and male testis and accessory glands. Separation of the corpora allata (CA) and corpora cardiaca followed by analysis of gene expression in the isolated glands revealed expression of the AeATr primarily in the CA. In the female CA, the AeATr mRNA levels were low in the early pupae, started increasing 6 hours before adult eclosion and reached a maximum 24 hours after female emergence. Blood feeding resulted in a decrease in transcript levels. The pattern of changes of AeATr mRNA resembles the changes in JH biosynthesis. Fluorometric Imaging Plate Reader recordings of calcium transients in HEK293 cells expressing the AeATr showed a selective response to A. aegypti allatotropin stimulation in the low nanomolar concentration range. Our studies suggest that the AeATr play a role in the regulation of JH synthesis in mosquitoes.